Effect of scan rate on corrosion inhibition of carbon steel in the presence of rice straw extract - potentiodynamic studies - Solhan Yahya,; Norinsan Kamil Othman,; Abd Razak Daud,; Azman Jalar, (Universiti Kebangsaan Malaysia, 2014)
The effect of scan rate on the accuracy of corrosion parameter in evaluating the efficiency of rice straw extract as corrosion inhibitor has been studied via potentiodynamic polarization measurement. Scan rate in the range of low (0.1-0.25 mV s-1), medium (0.5-1.0 mV s-1) and high (1.5-2.0 mV s-1) scan were carried out on the carbon steel in 1 M HCl. The corrosion parameters such as corrosion rate, polarization resistance and corrosion current density have been analyzed through Tafel polarization curve. High scan rate gave poor accuracy of corrosion parameter compared to medium and low scan. Medium scan at 1.0 mV s-1 has been chosen as the optimum scan rate due to the approached steady-state and small disturbance of charged current. As a result, the addition of rice straw extract in 1 M HCl has reduced the values of corrosion current density in both cathodic and anodic reactions signified the corrosion has been inhibited. The efficiency of rice straw extracts as a corrosion inhibitor offer good result as much as 86%.